The Relationship Between Self Empowerment and Quality of Life In People with Type 2 Diabetes Mellitus at Dr. Ir. Iwan Bokings - Salwia Hunowu; Nurdiana Djamaluddin; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2026)
Type 2 Diabetes Mellitus is a chronic disease with a significant increase in prevalence and has the potential to reduce quality of life due to complications and long-term management demands. Self-empowerment is an important component in disease management because it plays a role in improving patients' adaptability, confidence, and skills, which can further affect quality of life. This research aims to determine the relationship between self-empowerment and quality of life in patients with type 2 diabetes mellitus. This study is a quantitative study using a correlational analytical design and a cross sectional approach, involving 67 people who were taken using purposive sampling techniques. Respondents The results of the study showed that the majority of respondents had Self empowerment which was included in the sufficient category as many as 44 people (65.7%) and had quality of life in the moderate category as many as 46 people (68.7%). It shows that the better the level of self-empowerment that the respondents have, the better the quality of life they feel. Based on the results of the Chi-Square test, the p value was 0.009 (p < 0.05). This shows that there is a significant relationship between self-empowerment and quality of life in patients with Type 2 Diabetes Mellitus where the better the level of self-empowerment that the respondent has, the better the quality of life felt.